2013
DOI: 10.1179/1743294413y.0000000167
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ceria coating on corrosion behaviour of low alloy steel

Abstract: This paper investigates the effect of cerium oxide (CeO 2 ) coating on the high temperature corrosion behaviour of normalised and tempered 2?25Cr-1Mo steel in oxidation-sulphidation (SO 2 zO 2 ) mixed gas environment. The CeO 2 coating of two different coating thicknesses (150 and 300 mm) is prepared for experimental investigations. The isothermal corrosion study of uncoated and different CeO 2 coated specimens is carried out in SO 2 zO 2 environment at 973 K. The external scales of the post-corroded specimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Superficial coating of micro-sized ceria has proved to be effective in improving the oxidation resistance of stainless steels [14,15]. Ceria deposited on carbon steel [16] and low alloy steel [17] has also shown to improve the corrosion resistance of the substrate. Since the nature of the scale formed at high temperatures depends on the alloy chemistry as well as on the grain size of the coatings [18,19], so the nano-structured coatings are being extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…Superficial coating of micro-sized ceria has proved to be effective in improving the oxidation resistance of stainless steels [14,15]. Ceria deposited on carbon steel [16] and low alloy steel [17] has also shown to improve the corrosion resistance of the substrate. Since the nature of the scale formed at high temperatures depends on the alloy chemistry as well as on the grain size of the coatings [18,19], so the nano-structured coatings are being extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…The properties like porosities, cracking and residual stress on the microstructure can affect the high temperature oxidation and corrosion properties [8][9][10][11]. The different plasma sprayed ceramic oxide coating employed for oxidation/corrosion resistance has been reported by many researchers [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…1 The additions of Ce, Y, Zr, La (rare earth elements) or their oxides improve the high temperature oxidation resistance in chromia and alumina forming alloys due to a decrease in scale growth rate and improved resistance to scale spallation by improving the scale-alloy adhesion. [4][5][6][7][8] The improvement of oxidation resistance of nanocrystalline CeO 2 coated alloys over the microsize CeO 2 coated alloys has been reported in the past by several researchers. 9,10 Ghosh et al 9 have reported the tremendous improvement of oxidation resistance of nanocrystalline CeO 2 coated SS-304 stainless steel over micrometre size CeO 2 coated alloys.…”
Section: Introductionmentioning
confidence: 99%